The Role of Supply Chain Management in Service and Satisfaction to Loyalty in Transportation Business - Wahyuddin, M.; Wiyaning Putri, Angie; Soepatini, Soepatini; Agus Setyawan, Anton (International Journal of Supply Chain Management, 2020)
Abstract— Communication between buyers and sellers is central to the supply chain philosophy, which can improve customer satisfaction. The purpose of this study is to analyze the effects of supply chain on service scape and customer satisfaction to loyalty in transportation business. This study also analyze the role of satisfaction as mediating variable in the relationship between service scape and customer loyalty in supply chain process. Design of this study is quantitative, which developed an estimation model based on structural equation model to analyze the relationship among latent variables in this study. Data collection instruments using questionnaires were collected directly and online. The sampling technique was purposive sampling. It involves 115 respondents. Service scape is proven to have a significant effect on passenger satisfaction, but does not have a significant effect on passenger loyalty. Passenger satisfaction is proven to have a mediating role on the relationship between service scape and passenger loyalty. Service scape could be developed as a strategy to increase the quality of the service in transportation business. In this study, aesthetics, comfort, cleanliness and lay out of transportation vehicle and support plays a significant role to customer satisfaction. Service provider should redesign their business process based on supply chain process. Service scape represents an important aspect in service business, physical aspect in the intangibility. All factors in the supply chain aesthetics, comfort, cleanliness and lay out are operational variables of intangibility in service quality.